The influence of feeding on muscle tissues composition in cage reared bluefin tuna (Thunnus thynnus) - Miletić, Ivana, inženjerka ribarske tehnologije (Array, 2019)
Capture-based tuna aquaculture rates as one of the most important aquaculture activities in Cro-atia, where juvenile tuna are reared in cages for over a year long period in order to increase substan-tially their weight. The aim of this study was to assess the effect of length and intensity of feeding on biochemical composition (total fat, moisture, dry matter, carbohydrates and protein content) of tuna (Thunnus thynnus) white muscle tissues in newly caught tuna prior to feeding (NCTPF) versus far-med tuna kept in rearing circular cages in the Vela Grska Bay, Adriatic Sea (LAT 43°17’40,6984”N, LONG 016°28’58,4315”E (WGS84)) between 2001 and 2004. Farmed tunas from all cages were fed with the feed consisting of domestic small pelagic fish, or with mixtures containing North Sea herring (Clupea harengus) and Sardina pilchardus, for five months (cage 3), eight months (cage 4) or 21 months (cages 1 and 2). A low content of moisture and high content of dry matter including fat was observed in farmed tuna muscles compared to wild-caught tuna. In farmed tuna muscles, measured moisture was 55.26% in cage 1, 39.95% in cage 2, 54.64% in cage 3 and 49.70% in cage 4. These results are significantly lower than moisture measured in NCTPF (80.36%). Content of dry matter found in farmed tuna muscles also differed greatly between wild tuna (19.64%) and far-med tuna, but also between the cages (44.74% in cage 1, 60.05% in cage 2, 45.36% in cage 3 and 50.30% in cage 4). In NCTPF, muscle tissues total fat encompassed less than 1% of the total body weight, while it reached over 20% of total body mass in farmed fed tuna (20.62% in cage 1, 42.50% in cage 2, 20.97% in cage 3 and 20.57% in cage 4). These results demonstrate that high fat content can be achieved already after five months of intensive feeding.